Organizational Structure Settlement Research for Healthy Drink Company To Reduce High Turnover Research and Development Team : Case of Asa Cerra Company - Tulalessy, Timothya Jayce (Journal Integration of Management Studies, 2024)
Asa Cerra is a small-medium business that produces and markets healthy products. Currently, it focuses on turning mozzarella cheese waste called whey into healthy drinks that offer excellent probiotics and strains to improve digestive health. The company faced difficulties finding an R&D (research and development) team which had a negative impact on product development and sales. Through the 5-Whys analysis, it was concluded that an organizational structure that was not optimal was the main cause of the problem. This research uses a cyclical problem driven action research approach which iteratively collects data and implements changes based on the findings. SWOT (Strengths, Weakness, Opportunities, Threats) and TOWS (Threats, Opportunities, Weakness, Strengths) and the analysis is to identify internal and external factors that influence employee turnover. The ratio method and Analytic Hierarchy Process (AHP) is used to measure the relative impact of these factors and choose the most appropriate organizational structure. The findings of this research identify the most effective organizational structure to reduce the high turnover of R&D employees to support Asa Cerra's business continuity and product development. Keywords: Micro, Small and Medium Enterprises (MSMEs); Organizational Structure; SWOT and TOWS Analysis; Ratio Method; Analytical Hierarchy Process (AHP)